Radiological, Clinical, and Microbiological Manifestations of Pulmonary Tuberculosis Patients of a Secondary Hospital in Indonesia - Rusmajati, Jetty; Hanif, Aisyah Amanda; Desdiani, Desdiani (Sean Institute, 2025)
Tuberculosis (TB) remains a significant public health burden in Indonesia. Characterizing pulmonary TB's clinical, radiological, and microbiological features is vital to support timely and accurate diagnosis at secondary healthcare levels. This study aimed to analyze the clinical characteristics, radiological patterns, and microbiological status of pulmonary TB patients treated in secondary hospitals in Indonesia. This descriptive cross-sectional study retrospectively reviewed medical records of 58 adult patients with radiologically confirmed pulmonary TB, treated between January 2022 and December 2023. Data on demographics, symptoms, comorbidities, radiological features, and sputum smear results were analyzed. Associations between variables were tested using chi-square tests. Most patients were male (55.2%), with a mean age of 50.6 years. Previous TB history was recorded in 25.9% of cases, and 15.5% had comorbidities such as hypertension and diabetes. Cough (84.5%), fever (48.3%), and weight loss (41.4%) were the most common symptoms. Consolidation (89.7%) was the predominant radiological finding, often involving multiple lung zones (70.7%), with advanced lesions present in 77.6% of patients. Sputum smears were positive in 39.7% of cases. Pulmonary TB patients treated at secondary hospitals commonly present with advanced radiological lesions, significant comorbidities, and frequent smear-negative results. Strengthening radiological diagnostic capacity and integrated management of TB–diabetes comorbidity are essential to improve case detection and outcomes.